Petrology of the Gillis Mountain pluton, Cape Breton Island, Nova Scotia - Barr, S. M.; O'Beirne, A. M. (Canadian Journal of Earth Sciences, 1981)
The Gillis Mountain pluton is a small composite granitoid intrusion in southeastern Cape Breton Island. It is one of the few plutons of known Devonian age in Cape Breton Island and is particularly significant because of the presence of Cu–Mo mineralization with porphyry affinities. The pluton consists of three main phases (quartz monzodiorite, porphyritic granite, and fine-grained granite) with minor late dykes of granite, granitic porphyry, and aplite. These phases probably represent a differentiation sequence from an 'I-type' parent magma of calc-alkalic affinity. All phases have been affected by phyllic and possibly potassic alteration, presumably related to the mineralization processes. However, this hydrothermal activity appears to be little reflected in the bulk chemistry of the pluton, except possibly in increased barium content and large standard deviations in the metallic elements and sulphur.